Political Imprisonment and the CONINTES Plan. A Local Analysis: Mar del Plata, Buenos Aires Province (1958-1962) (Quinto Sol, 2025)
The Plan of Internal State Commotion (CONINTES) was implemented during the government of Arturo Frondizi (1958-1962) in Argentina in a context of labor unrest and union conflict. It established the subordination of the provincial police to the Armed Forces, thus enabling their participation in internal repression. This article reconstructs the case of the "CONINTES prisoners" detained at the Naval Base in the city of Mar del Plata, province of Buenos Aires. Its main objective is to analyze this experience of political imprisonment from a precise identification of the actors involved and the repressive practices implemented in this Navy department. The choice of this analytical perspective seeks to establish a dialogue between the national context and the specific political and social dynamics of the local space. The main corpus of sources is made up of complaints of illegal harassment made by the detainees and the local press.
Keywords: political prisoners; repression; Armed forces; violence